E-Proceeding for Asian Conference on Business, Economics and Social Science (ACBESS) 2021 / Mohamed Saladin Abdul Rasool ... [et al.] - Abdul Rasool, Mohamed Saladin (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
ASIAN CONFERENCE ON BUSINESS, ECONOMICS AND SOCIAL SCIENCES (ACBESS 2021) with the theme “Contemporary Research Insights in the area of Business, Economics and Social Science Development”. Due to this global pandemic caused by Covid-19, the task of organizing such an event was challenging, forcing us all to work under unfamiliar conditions and situations. These changes have made us adapt and familiarize ourselves in using technological platforms to make this event successful. Therefore, I would like to congratulate the committee members and the UiTM Cawangan Melaka, Malaysia to organize this event in the new norm successfully. The COVID-19 pandemic has affected people worldwide, leading to the near-total closures of schools, universities, and colleges. Nevertheless, the spirit of producing inventions and innovations that are beneficial for society is still ongoing even through this pandemic. ACBESS provides a platform for academicians, researchers, and postgraduate students to generate creative and innovative ideas even in the middle of the Covid-19 pandemic. Although this event could not be organized in the traditional face-to-face approach in which we have, we have adapted and embraced these changes to remain competitive and relevant in the Fourth Industrial Revolution (IR 4.0). The Industrial Revolution 4.0 (IR 4.0) is the digitalisation of industries that would create new job opportunities for future graduates. IR 4.0 has given a new impetus to the educational transformation that is Education 4.0, which could affect all the domains of the pedagogical theory of the Bloom's model (e.g. Cognitive, Affective and Psychomotor) in terms of significant change in the content, delivery, pedagogy, structure and management of education. Changes in the human resources produced by the Education 4.0 are more likely to be highly creative, data literate and critical thinkers. Thus, to ensure that these human resources remain relevant in IR 4.0, ACBESS has focused on various contemporary sub-themes that hope to create new knowledge in the area and further cultivate collaborations with the people who have been participating in this event. I believe that the efforts showed by the faculty, committee members, jointly distinguished universities and all participants will have a significant impact on the socio-economic development of the global community and develop novel ideas and methods to be successful in the field of business. I hope that the organization of this event can be continued in the future to build research interests and networking while creating and presenting new ideas and innovations that can be commercialized. I want to acknowledge the exceptional efforts of the presenters and participants who have realized the aspiration to think creatively, make critical analyses, always think forward, innovative, and resilient to face future challenges. finally, I would like to once again congratulate the efforts and cooperation of all parties, especially those who have made this event successful. Hopefully, this little effort of ours will be rewarded many times over by God the Almighty, In shaa Allah.